Human, cattle and goat blood as substitutes for sheep blood in blood-supplemented culture media - GN Dilrukshi; UN Jayewardane; F Sajidha; DMBT Dissanayake (Sri Lankan Journal of Infectious Diseases, 2018)
Introduction and Objective: Sheep blood is the recommended type of blood for supplementation of agar media. In Sri Lanka, due to lack of availability of sheep blood, expired citrated human blood is used which gives poor haemolysis and causes difficulties in identification of some organisms. In addition, human blood contains antibodies and other antibacterial factors including antibiotics which may inhibit bacterial growth. Human blood may also contain blood borne pathogens which could be a risk for laboratory staff. The objective of this study was to explore available alternatives in the Sri Lankan setting. Methods: Clinical isolates and standard strains of Streptococcus pyogenes, Streptococcus agalactiae, Streptococcus pneumoniae and Haemophilus influenzae were tested for growth, identification characteristics and antibiotic susceptibility on human, cattle, goat and sheep blood agars. The performances were compared. Identification of Listeria monocytogenes as well as Streptococcus agalactiae was carried out using the CAMP test. Results: All tested organisms gave similar isolation rates at the tested dilutions in the four tested agar plates. Human blood gave noticeably smaller colonies. S. pyogenes and S. agalactiae gave equally large zones of beta-haemolysis and S. pneumoniae gave obvious alpha-haemolysis on all animal blood agar plates. Both types of haemolysis were faint on human blood. Typical arrow head shape haemolysis for S. agalactiae and match-head shape haemolysis for Listeria were seen in the CAMP test on the three animal blood agar plates whereas human blood gave negative results. All blood agar plates gave comparable positive results in the satellitism test for H. influenzae. There was no difference in bacitracin and optochin sensitivity tests for identification of S. pyogenes and S. pneumoniae respectively. Inhibitory zones were unreadable when antibiotic susceptibility was done for H. influenzae on goat and cattle chocolate agar. Sheep and human chocolate agar were inferior to Haemophilus test medium. ABST results were equivalent but goat blood gave hazy, irregular margins for other organisms. Conclusions: Cattle and goat blood show similar performance to sheep blood in growth and identification tests for common fastidious pathogens. Cattle blood is equivalent to sheep blood for ABST, but goat blood is inferior.